Municipal Market Halls in Cyprus, c. 1870-1970: Intersecting Traditions and the Dynamics of Colonial Modernity - Erogul, Halide; Pulhan, Hifsiye (Sage Publications Inc, 2025)
Starting near the close of the nineteenth century, the construction of permanent, covered markets in Cyprus represented a substantial shift away from the traditional open-air street marketplace or bazaar. Market life in Cyprus had long been influenced by the prevailing civilizations, as the island lies at the crossroads of historic trade routes in the Eastern Mediterranean. However, the definitive form of the marketplace emerged with the modern governance and urban reforms introduced during British colonial rule (1878-1960). This new form was the Municipal Market Hall (MMH), where occidental and oriental retail codes of conduct, ethics, and traditions intermingled. The coexistence of Medieval, Ottoman, and British colonial elements in retail spaces and practices gave rise to a distinctive urban form and served as evidence of a multifaceted public life shaped by the dominant forces of the modern era. Thus, MMHs became key artifacts associated with colonial modernity in Cyprus.
Keywords: market life; colonial modernity; Ottoman bazaar traditions; Municipal Market Hall; Cyprus